Tìm nguyên hàm của hàm số \(f(x)=\mathrm{e}^x\left(1+\mathrm{e}^{-x}\right)\).
\(\displaystyle\int f(x)\mathrm{\,d}x=\mathrm{e}^x+1+C\) | |
\(\displaystyle\int f(x)\mathrm{\,d}x=\mathrm{e}^x+x+C\) | |
\(\displaystyle\int f(x)\mathrm{\,d}x=-\mathrm{e}^x+x+C\) | |
\(\displaystyle\int f(x)\mathrm{\,d}x=\mathrm{e}^x+C\) |
Chọn phương án B.
Ta có: \(f(x)=\mathrm{e}^x\left(1+\mathrm{e}^{-x}\right)=\mathrm{e}^x+1\).
Suy ra \(\displaystyle\int f(x)\mathrm{\,d}x=\displaystyle\int\left(\mathrm{e}^x+1\right)\mathrm{\,d}x=\mathrm{e}^x+x+C\).